Reactions of Some 1,1,2-Trihalocycloalkanes with Morpholine - Hari Prasad, S.; Nagendrappa, Gopalpur (Asian Journal of Chemistry, 2010)
The five to eight membered 1,1.2-trihalocycloalkanes 1 to 5 react with greater than seven equivalents of morpholine under reflux conditions to yield single clean elimination-substitution products: the 2-halo-3-morpholinyl-1-cycloalkenes 7-9.